AAV micro-dystrophin gene therapy alleviates stress-induced cardiac death but not myocardial fibrosis in >21-m-old mdx mice, an end-stage model of Duchenne muscular dystrophy cardiomyopathy - Bostick, Brian (2012)
Duchenne muscular dystrophy (DMD) is a fatal genetic disease caused by the absence of the sarcolemmal protein dystrophin. Dilated cardiomyopathy leading to heart failure is a significant source of morbidity and mortality in DMD. We recently demonstrated amelioration of DMD heart disease in 16 to 20-m-old dystrophin-null mdx mice using adeno-associated virus (AAV) mediated micro-dystrophin gene therapy. DMD patients show severe heart disease near the end of their life expectancy. Similarly, mdx mice exhibit profoundly worsening heart disease when they reach beyond 21 months of age. To more rigorously test micro-dystrophin therapy, we treated mdx mice that were between 21.2 to 22.7-m-old (average, 22.1 ± 0.2 months; N=8). The ΔR4-23/ΔC micro-dystrophin gene was packaged in the cardiotropic AAV-9 virus. 5 × 10(12) viral genome particles/mouse were delivered to mdx mice via the tail vein. AAV transduction, myocardial fibrosis and heart function were examined 1.7 ± 0.2 months after gene therapy. Efficient micro-dystrophin expression was observed in the myocardium of treated mice. Despite the robust dystrophin expression, myocardial fibrosis was not mitigated. Most hemodynamic parameters were not improved either. However, ECG abnormalities were partially corrected. Importantly, treated mice became more resistant to dobutamine-induced cardiac death. In summary, we have revealed for the first time the potential benefits and limitations of AAV micro-dystrophin therapy in end-stage Duchenne dilated cardiomyopathy. Our findings have important implications for the use of AAV gene therapy in dilated cardiomyopathy and heart failure.